Entrepreneurial Skills and Spirit of Students In Higher Vocational Colleges in Guangdong, China - Huang, Yina (Pacific International Journal, 2024)
The COVID-19 pandemic has significantly impacted the employment landscape, making entrepreneurship a critical alternative for students in higher vocational colleges in Guangdong Province, China. This study investigates the relationship between entrepreneurial spirit and skills and entrepreneurial education among these students. Utilizing a sample of 623 students and 23 teachers from three higher vocational colleges, the research employs a descriptive-correlational-quantitative approach. The findings reveal a substantial interaction between entrepreneurial skills and education, demonstrating that entrepreneurship education effectively enhances students' entrepreneurial abilities and mindset. Teachers are integral in delivering this education, focusing on cultivating both professional skills and an entrepreneurial spirit. The study underscores the necessity for robust entrepreneurship education to prepare students for the challenges of the modern economy, promoting self-employment and job creation. By developing strategic planning, financial management, relationship management, and problem-solving skills, students are better equipped to navigate the complexities of starting and managing their own businesses. This research contributes to the understanding of how educational practices can foster a thriving entrepreneurial ecosystem within vocational institutions, ultimately supporting economic growth and innovation. The results highlight the importance of comprehensive entrepreneurial education in vocational colleges to ensure students are well-prepared for future entrepreneurial endeavors.